Optimum centerpivot irrigation system design with tillage effects - Mohamoud, Y.; McCarty, T.R.; Ewing, L.K. (American Society of Civil Engineers, 1992)
A method is presented for designing the outer‐end sprinkler of a center‐pivot irrigation system to prevent surface runoff. The smallest wetted diameter, for which soil infiltration capacity equalled or exceeded nozzle application rate, was determined by equating a nozzle application rate relationship and a Green and Ampt infiltration rate relationship. The computed wetted diameter was used in developing relationships to select nozzle type, orifice diameter, and operating pressure. Sensitivity analysis determined that wetted diameter is primarily sensitive to soil characteristics related to infiltration and to evapo‐transpiration rate. Examples illustrated variations in irrigation system design because of tillage system. Greater operating pressure of an irrigation system is necessary to prevent runoff if the tillage system does not prevent soil surface crusting or compaction by raindrops. Considering a no‐till system resulted in the selection of a low‐pressure impact sprinkler instead of a conventional high‐ or medium‐pressure impact sprinkler. Therefore, the developed methodology can be used to design the optimum center pivot irrigation system for given soil, climate, cropping pattern, and tillage practices.